A hedonic approach to estimating the supply of variety attributes of a subsistence crop - Edmeades, Svetlana (International Food Policy Research Institute, 2006)
The paper extends the household hedonic model, as a non-market valuation tool, by estimating a supply function for variety attributes of a subsistence crop in a developing country. The model is applied to bananas in Uganda, making use of disaggregated data on variety-specific farm-gate banana bunch prices and attributes. The hedonic analysis is applied at the farm-gate, the first link in the market chain, while accounting for the semi-subsistence nature of banana producing households. Within the framework of the agricultural household, where consumption and production decisions are non-separable, prices reflect the implicit marginal valuation of both consumption and production attributes jointly. The paper is motivated by the need to quantify the value of banana attributes in light of targeted efforts for variety improvement. Whether variety improvement will pay-off at the market level requires a more detailed examination of the relative worth of banana attributes within the structure of consumer preferences and production technologies related to bananas in Uganda. By revealing important price-attribute relationships, the findings provide guidance for future crop improvement efforts and diversification choices, while taking into account implicit market signals for output characteristics.